Hyperhomocysteinemia is key for increased susceptibility to PND in aged mice - Guangchao Zhao; Jiao Deng; Yuan Shen; Peng Zhang; Hailong Dong; Zhongcong Xie; Lize Xiong (Annals of Clinical and Translational Neurology, 2019)
Abstract Background Postoperative neurocognitive disorder (PND) is a severe postoperative complication with no effective therapy that affects up to 19–52% of senior patients. Age and surgery type have been identified as risk factors. However, what caused the increased risk in the elderly is poorly understood. Methods We utilized a PND model in aged mice undergoing experimental laparotomy with general anesthesia to evaluate the causal relationship between hyperhomocysteinemia and increased PND susceptibility. PND was assessed by Novel Object Tasks, Fear Conditioning Tests, and Barnes Maze Tests. Serum homocysteine (Hcy) as well as vitamin B12 and folate acid levels were tested before, immediately after surgery and from day 1 to day 29 after surgery by ELISA. The effectiveness of preventative strategy including diet supplementation of vitamin B12 + folic acid (Vit B12 + FA) and S‐adenosylmethionine (SAM) injection targeting hyperhomocysteinemia were also tested. Results PND in aged mice lasted for at least 2 weeks after experimental laparotomy, which was not observed in young adult mice. Serum Hcy results indicated a significant correlation between postoperative cognitive performance and perioperative Hcy level. Preoperative supplementation with VB12 and folic acid (FA) in the diet or S‐adenosylmethionine (SAM) injection reduced perioperative serum Hcy level and inhibited the development of PND in aged mice. Conclusions Serum homocysteine accumulation is a fundamental cause for increased susceptibility of PND in aged mice. Preoperative diet supplementation of VitB12 + FA can effectively reduce PND in aged mice, which may be a promising prophylaxis treatment in clinical settings.